Polymer brushes for improvement of dry adhesion in biomimetic dry adhesives. (21st April 2014) - Chaudhary, Omer Javed; Calius, Emilio; Kennedy, John V.; Travas-Sejdic, Jadranka
Geckos' feet are extensively micro-structured, enabling geckos to adhere strongly to most surfaces and perform various manoeuvres even while upside down. Inspired by the structure of geckos' feet, a large number of biomimetic dry adhesives have been reported. Polymers brushes can offer a molecular scale attachment to surfaces; here we studied the effect of polymer brushes on adhesion. Atom transfer radical polymerisation (ATRP) was used to graft poly(butyl acrylate) brushes on a poly(dimethylsiloxane) (PDMS) surface using a surface-bound ATRP initiator. Growth of the polymer brushes was verified by ATR-FTIR spectroscopy. To study the effect of polymer brushes, the samples were tested for pull-off adhesion with and without the grafted chains. The polymer-grafted PDMS showed an increase in adhesion compared to unmodified PDMS. Results suggest that carefully selected polymer brushes will enhance the adhesion of microstructured biomimetic adhesives.